Vitamin D Supplementation and Hemoglobin Levels in Hypertensive Patients: A Randomized Controlled Trial - Jana B. Ernst; Andreas Tomaschitz; Martin R. Grübler; Martin Gaksch; Katharina Kienreich; Nicolas Verheyen; Winfried März; Stefan Pilz; Armin Zittermann (International Journal of Endocrinology)
Epidemiological evidence suggests that circulating 25-hydroxyvitamin D (25OHD) levels are inversely associated with hemoglobin (Hb) levels and anemia risk. We evaluated whether vitamin D supplementation improves Hb levels and reduces anemia risk in hypertensive patients. Two hundred patients with 25OHD levels <75 nmol/L who attended the Styrian Vitamin D Hypertension Trial were included, of whom 188 completed the trial. Patients randomly received 2800 IU vitamin D3 daily or a matching placebo for eight weeks. Initially, the prevalence of anemic status (Hb levels <12.5 g/dL) and deficient 25OHD levels (<30 nmol/L) was 6.5% and 7.5%, respectively. All anemic patients had 25OHD levels >50 nmol/L. The mean (95% confidence interval) vitamin D effect on Hb levels was 0.04 (−0.14 to 0.22) g/dL (P=0.661). Moreover, vitamin D treatment did not influence anemic status significantly (P>0.999). Likewise, vitamin D had no significant effect on Hb levels in the subgroups of anemic patients or in patients with initial 25OHD levels <30 nmol/L. In conclusion, a daily vitamin D supplement of 2800 IU for eight weeks did not improve Hb levels or anemic status in hypertensive patients. Future trials should focus on anemic patients with deficient 25OHD levels (e.g., <30 nmol/L). This trial is registered with clinicaltrials.gov [NCT02136771].